Analisis Kemampugaruan dan Kemampugalian Batuan Peridotit Kabupaten Morowali Utara, Provinsi Sulawesi Tengah - Amritzal Nur Firdaus; Isman Saleh; Iswandi Utama (OPHIOLITE: Jurnal Geologi Terapan, 2025)
In lateritic nickel mining, peridotite rock serves not only as the primary source of nickel laterite but also plays a crucial role in slope design and the development of mining infrastructure, such as the construction of mine roads. Additionally, economically non-viable peridotite can be repurposed as fill material or construction raw material if it meets specific technical criteria. This study aims to analyze the ripperability and abrasiveness of peridotite rock in the research area to determine the most effective excavation method. The analysis was conducted using joint spacing data and rock strength obtained through measurements of rock mass discontinuities using the scanline survey, uniaxial compressive strength (UCS) tests, and point load tests. The findings indicate that the rock in the study area can be classified into three main categories based on joint spacing and strength: easy ripping, hard ripping, and very hard ripping. Based on the analysis, the recommended heavy equipment includes Bulldozer models D7G and D8K, which are suitable for the rock rippability categories identified at the site. Rocks with high strength values exhibit high abrasiveness, leading to accelerated wear on heavy machinery. Therefore, selecting wear-resistant equipment and implementing more intensive maintenance planning are essential to improving operational efficiency in the study area.